123k views
0 votes
1. Simplify 3(2x - y) + 6y.
5x + 7y
6x + 3y
2x + 3y
6x - 7y

2 Answers

2 votes


\huge\boxed{Hi\: there!}

Here, we use the Distributive Property:


a(b+c)=ab+ac

3(2x-y)+6y=6x-3y+6y

Combine like terms:

6x+3y


\huge\boxed{Therefore,\: our \:equation\: is:6x+3y}


\huge\bf{Good \:luck \:with \:your \: studies! :)\\~Unknown Dreamer}

User Imants Volkovs
by
5.7k points
0 votes

Answer:

6x + 3y

Explanation:

3(2x - y) + 6y ← distribute parenthesis by 3

= 6x - 3y + 6y ← collect like terms

= 6x + 3y

User Mr Hyde
by
5.1k points